OC-04 - Tissue factor positive microvesicles activate platelets in vitro and in vivo and enhance thrombosis in mice. Issue 140 (April 2016) - Hisada, Y.; Geddings, J.E.; Boulaftali, Y.; Getz, T.M.; Whelihan, M.; Fuentes, R.; Dee, R.; Cooley, B.C.; Key, N.S.; Wolberg, A.S.; Bergmeier, W.; Mackman, N.
Abstract : Introduction: Cancer patients have a 4- to 7- fold increased risk of venous thromboembolism (VTE) compared with general population. Most tumor cells express tissue factor (TF) and constitutively release small membrane microvesicles called tumor microvesicles (TMVs). Clinical studies have shown that circulating MP-TF activity is associated with VTE in pancreatic cancer but not in other types of cancer. Thrombin is a potent platelet agonist and activates platelets via protease activated receptors (PARs). Aim: To determine the contribution of the TF + TMV-thrombin-platelet pathway to cancer-associated thrombosis. Materials and Methods: A human pancreatic adenocarcinoma cell line expressing high levels of TF (BxPc-3) was selected to study the effect of TF + TMVs on platelet activation and thrombosis. Results: TF + TMVs induced platelet activation in vitro in a thrombin-dependent manner. The presence of orthotopically grown BxPc-3 tumors in mice was associated with increased levels of thrombin-antithrombin III complexes (TATc) and larger thrombi in an inferior vena cava stenosis model compared with control mice. Furthermore, injection of BxPc-3 TF + TMVs into mice triggered platelet activation and enhanced venous thrombosis in a TF-dependent manner. Importantly, BxPc-3 TF + TMV-enhanced thrombosis was reduced in Par4-deficient mice and wild-type mice treated with the platelet inhibitor clopidogrel, suggesting that platelet activation was required for the enhanced thrombosis. Conclusions: These studies suggest that platelet inhibitors may reduce thrombosis in cancer patients with elevated levels of TF + TMVs.